PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMP NEGERI 1 GOMO TAHUN PELAJARAN 2023/2024 - Eka setiawan Lase; Adrianus Bawamenewi; Amstrong Harefa; Berkat Persada Lase (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Information and Communication Technology is one of the technologies that must be developed in the world of education. This research uses a qualitative method by taking a descriptive approach. The research instrument in this study is the researcher himself by observing, asking, listening, requesting and collecting research data by using a cellphone as a tool to record all conversations, resulting images as real evidence, and a notebook which functions to record conversations with the data source or informant. The data collection techniques used were interviews, observation and documentation. The results of the research and discussion concluded that: first, the use of information and communication technology at SMP N 1 Gomo school, namely, by integrating information and communication technology into the school curriculum. This is done by teachers and students to facilitate the learning process more effectively by utilizing information and communication technology (ICT) as a tool to support learning in various subjects. Second, the importance of (ICT) in learning is very influential, with the presence of (ICT) in schools teachers and students can quickly interact in the teaching and learning process. Then there, the use of information technology as a student learning resource is reflected in its use as a learning resource at home and its use in the learning process. Third, efforts to overcome obstacles to the use of ICT in schools are: